2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32174
|View full text |Cite
|
Sign up to set email alerts
|

Board 105: Exploring Enculturation in the First-year Engineering Program (Year III)

Abstract: Station (TEES). She received a Ph.D. in Educational Psychology with specialties in Gifted Education and a M.S.Ed. in Educational Psychology with specialties in Research Methods and Measurement both from Purdue University. She also holds a M.S. in Astronomy and Astrophysics and a B.S. in Astronomy and Meteorology both from Kyungpook National University in South Korea. Her work centers on engineering education research, as a psychometrician, program evaluator, and institutional data analyst. She has research int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…First-year and first-semester courses are the general introduction to the major disciplines that students get when they first enter college. First-year engineering (FYE) courses in particular have been focusing on getting engineering students a closer experience to the engineering profession 17,18 . The FYE courses engage students in engineering activities to get them to better learn the engineering disciplines as intended by experiential learning theory (ELT) 19,20,21 .…”
Section: The Coursementioning
confidence: 99%
See 2 more Smart Citations
“…First-year and first-semester courses are the general introduction to the major disciplines that students get when they first enter college. First-year engineering (FYE) courses in particular have been focusing on getting engineering students a closer experience to the engineering profession 17,18 . The FYE courses engage students in engineering activities to get them to better learn the engineering disciplines as intended by experiential learning theory (ELT) 19,20,21 .…”
Section: The Coursementioning
confidence: 99%
“…The FYE courses engage students in engineering activities to get them to better learn the engineering disciplines as intended by experiential learning theory (ELT) 19,20,21 . The university in this study made major changes in the design of their FYE courses from project-based 22,17,18 to a more subject-specific format 23,24 in 2018 to improve retention.…”
Section: The Coursementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many introductory engineering courses worldwide have a component of programming or computational thinking. A preliminary study of enculturation to the engineering profession found that computational thinking was deemed a critical area of development at the early stages of instruction (Mendoza Diaz et al, 2018, 2019Richard et al, 2016;Wickliff et al, 2018).…”
Section: Computational Thinking Diagnostics For First-year Engineering Students: Year Imentioning
confidence: 99%
“…The FYE courses engage students in engineering activities to get them to better learn the engineering disciplines as intended by experiential learning theory (ELT) 19,20,21 . The university in this study made major changes in the design of their FYE courses from project-based 22,17,18 to a more subject-specific format 23,24 in 2018 to improve retention.…”
Section: The Coursementioning
confidence: 99%